2018
DOI: 10.1089/pho.2018.4473
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Skeletal Muscle Strain Lesion Induced by Stretching in Rats: Effects of Laser Photobiomodulation

Abstract: Laser photobiomodulation reduced skeletal muscle edema as well as cytokines and CRP, leading to a significant reduction in inflammatory markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Twenty-two studies used passive stretching, satisfying the definition of a movement applied by an external force [ 20 41 ]. All passive stretching studies anesthetized the animals to manual stretching or stretching achieved with a mechanical device [ 20 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-two studies used passive stretching, satisfying the definition of a movement applied by an external force [ 20 41 ]. All passive stretching studies anesthetized the animals to manual stretching or stretching achieved with a mechanical device [ 20 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies used passive stretching, satisfying the definition of a movement applied by an external force [ 20 41 ]. All passive stretching studies anesthetized the animals to manual stretching or stretching achieved with a mechanical device [ 20 41 ]. Of the 22 studies, fourteen explored the effect of dynamic muscle activation with a protocol of lengthening and shortening contractions/cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, they concluded that the laser reduced skeletal muscle edema as well as cytokines, and CRP then led to a significant reduction in inflammatory markers. 11 Through a study guided by Carvalho et al, 15 male rats were distributed into three groups: control group (C), induced myositis without treatment (MI), and treated induced myositis (MT), for seven days. The induction of acute myositis was done with 1% acetic acid by the intramuscular route.…”
Section: Discussionmentioning
confidence: 99%
“…After the first 24 h postlesion, there is little evidence about the usefulness of pulsed ultrasound therapy (UST) (1 W/cm 2 ) [ 13 ] (often used as cryo-ultrasound, with the adjunct of ice therapy) and low-level laser therapy (LT) (500 mW/cm 2 ) [ 9 , 35 , 36 , 37 ].…”
Section: Muscle Injuries Rehabilitationmentioning
confidence: 99%